2021
DOI: 10.1111/jgh.15666
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of cold snare polypectomy for superficial non‐ampullary duodenal epithelial tumors

Abstract: Background and Aim:The effectiveness of cold snare polypectomy (CSP) for superficial non-ampullary duodenal epithelial tumors (SNADETs) regarding long-term outcomes is not fully clarified. This study aimed to investigate long-term outcomes of CSP for SNADETs. Methods: Patients diagnosed with sporadic SNADETs and treated with CSP at Chiba University Hospital between March 2015 and May 2018 were retrospectively analyzed. Long-term outcomes, short-term outcomes, and adverse events were investigated. Results: In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Okimoto et al [ 12 ] reported the outcomes of CSP for 47 lesions with a median endoscopic size of 4 mm. The en-bloc and R0 resection rates were 97.8% and 70.3%, respectively.…”
Section: Review Of Endoscopic Treatment For Snadetsmentioning
confidence: 99%
“…Okimoto et al [ 12 ] reported the outcomes of CSP for 47 lesions with a median endoscopic size of 4 mm. The en-bloc and R0 resection rates were 97.8% and 70.3%, respectively.…”
Section: Review Of Endoscopic Treatment For Snadetsmentioning
confidence: 99%
“…While no long-term follow-up data were available for these above reported studies, Okimoto et al [ 51 ] performed a single center retrospective study to evaluate long-term outcomes of CSP for SNADETs. 29 patients underwent CSP for 37 sporadic duodenal adenomatous lesions; mean size was 4.4 mm[ 51 ]. The en bloc and R0 resection rates were 97.3% and 70.3%, respectively.…”
Section: Csp In Duodenummentioning
confidence: 99%
“…The relapse free survival rate per lesion after 12 mo was 97.1%. Neither delayed bleeding no perforation was reported and no procedure-related death occurred[ 51 ].…”
Section: Csp In Duodenummentioning
confidence: 99%
“…Cold snare EMR (cold EMR) has already been shown to be a safe and viable option for resecting larger polyps in the colon 6. Preliminary small studies evaluating cold EMR in the duodenum have reported recurrence rates of 0%–45% for large adenomas 7–12. These studies have not included direct comparison with hot EMR.…”
Section: In More Detailmentioning
confidence: 99%